Non-Inseminated Queens Have Worker-Like Behaviors in Colonies of Fungus-Growing Ants, Mycetomoellerius turrifex Wheeler (Attini, Hymenoptera) - Murakami, Takahiro (Sociobiology, 2020)
In eusocial Hymenoptera such as ants, bees, and wasps, the queen numbers are fundamentally important to maintain the social systems. In Texas, USA, a fungus growing ant, Mycetomoellerius turrifex Wheeler (1903) (the genus name was changed from Trachymyrmex to Mycetomoellerius in 2019 (Solomon et al., 2019)) was observed to have several non-inseminated queens that wandered outside the nest long after the mating season. However, the evolutionary and ecological factors causing the occurrence of such non-inseminated queens are still unclear. Thus, I examined the worker-like behaviors of non-inseminated queens of M. turrifex in Texas. Fifteen ant colonies were collected over three years, between 1999 and 2001. The frequencies of non-inseminated queens, workers, and broods, as well as the depths of nest chambers, were observed in each collecting year. In Nov. 1999 and May 2000, multiple nests contained queens that did not mate with males within their nests. These nests had a relatively larger colony size than those collected in Oct. 2001. Conversely, the colonies collected in Oct. 2001 were completely monogynous, i.e., there were no non-inseminated queens in the nests. Behavioral observations of each female revealed that the non-inseminated queensbehaved significantly differently from the workers and the inseminated queens. The behaviors that distinguished different female castes were mutualistic fungus garden care, digging of nest floors, guarding, and resting in the nest. These data suggest that queens failed to mate due to severe environmental fluctuations in southern Texas, but were accepted by the colony as a temporary labor force.